CoIII2DyIII2 single molecule magnet with two resolved thermal activated magnetization relaxation pathways at zero field - Funes, Víctor Alejandro (2014)
The new complex [CoIII2DyIII 2(OMe)2(teaH)2(Piv)6] in the CoIII2DyIII2 family, shows two well resolved thermal activated magnetization relaxation pathways under AC experiments in zero DC field. Fitted crystal field parameters suggest that the origin of these two pathways relies on two different excited mJ sub-levels.